Defence Against Weapons of Mass Destruction Terrorism - Aytaç, Osman (IOS Press, 2013)
In Defence Against Weapons of Mass Destruction Terrorism the editors examined the class of Weapons of Mass Destruction (WMD) for terrorist use, and have found that their effects range from serious nuisance value up to catastrophic destruction of a large urban area. There are some differences in the effects depending on whether they are used against military or civilian targets, whether they are used from inside the target area or outside, and between those weapons for which MOPP (Mission Oriented Protective Posture) gear can provide useful protection (Biological Weapons, Chemical Weapons) and those for which it often cannot (radiation, nuclear explosions). These are useful ways to begin thinking about establishing protocols for protecting our armed forces and the civilian population they are sworn to defend.